Special material for motor outgoing line
By using a combination of modified nanofillers, micro-reinforced fillers and conductive fillers in the motor lead wire material, the mutual combination and structure of the materials are optimized, and the shortcomings of existing materials in insulation performance, conductive network stability, heat resistance and mechanical properties are solved, and higher performance integration is achieved.
Patent Information
- Application Number
- CN202510315822.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing motor lead wire materials have shortcomings in insulation performance, conductive network stability, heat resistance and mechanical properties, and are difficult to meet the needs of modern complex applications.
The combination of polyimide matrix material and nano-scale low dielectric constant fillers, micro-scale reinforced fillers, conductive fillers and interface regulators is used to optimize the mutual bonding and structure of the materials through surface modification and hot pressing forming technology.
It significantly improves the insulation performance, conductivity, heat resistance and mechanical properties of the material, and solves the problems of high leakage current, unstable conductive network, limited heat resistance and poor mechanical properties.
Smart Images

Figure CN119842232A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of motor lead wires, in particular to a special material for motor lead wires. Background Art
[0002] As a key component of motor operation, the material properties of the motor lead wire directly affect the operating stability and life of the entire system. In the prior art, the insulation material of the motor lead wire is usually composed of a polymer matrix and a reinforcing filler, with the goal of optimizing insulation performance, conductivity, heat resistance and mechanical properties at the same time. Although the prior art has made certain progress in these areas, there are still many technical bottlenecks when facing modern complex application requirements.
[0003] In the prior art, in order to improve the insulation performance of the motor lead wire, a composite system of a polymer matrix combined with a filler is usually used. However, due to the uneven distribution of the filler, poor interface bonding and large filler particle size, the traditional micron-sized filler is prone to agglomeration in the matrix, forming an area of uneven dielectric performance. According to the dielectric constant theory of Maxwell's equations, the interface defects between the filler and the matrix will lead to a local electric field concentration effect, increase the polarization intensity, and thus significantly improve the dielectric constant of the composite material. Due to the weak interface bonding between the traditional filler and the polyimide matrix, microscopic gaps are formed between the filler and the matrix. These gaps are prone to become leakage paths in a high voltage environment, increasing the leakage current.
[0004] In some motor lead wire materials, conductivity and insulation need to be taken into account to meet multifunctional requirements. In the prior art, carbon black is mostly used as a conductive filler. It is a zero-dimensional particle that relies on particle accumulation to form a conductive network. However, the contact area between carbon black particles is limited, and a continuous conductive path cannot be formed at a low filler content, resulting in low conductivity; Modern motor systems mostly operate in high temperature, high pressure or other harsh environments, which places higher heat resistance requirements on motor lead wire materials. Glass fiber or carbon fiber is often used as reinforcing fillers in the existing technology, but the heat resistance of these materials is limited. The softening point of glass fiber is about 500°C, and it cannot operate stably in higher temperature environments. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a special material for motor lead wires, which solves the problems of insufficient insulation performance, unstable conductive network, limited heat resistance and poor mechanical properties in motor lead wire materials.
[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a special material for motor lead wires, comprising the following components by weight percentage: polyimide matrix material: 50-70%, nano-level low dielectric constant filler: 5-12%, micron-level reinforcing filler: 10-20%, conductive filler: 3-8%, interface regulator 0.5-2%, and processing aid 1-3%.
[0007] Preferably, the polyimide matrix material is a fluorine-containing polymer, and the fluorine-containing polymer is polytetrafluoroethylene, perfluoroethylene propylene or a mixture thereof.
[0008] Preferably, the nano-scale low dielectric constant filler is silicon dioxide particles with a particle size of 10-50 nm, and the silicon dioxide particles are surface-modified by a silane coupling agent.
[0009] Preferably, the micron-sized reinforcing filler is aluminum oxide particles, and the particle size of the aluminum oxide particles is in the range of 1-10 μm.
[0010] Preferably, the conductive filler is one or more of carbon nanotubes, graphene or silver nanowires.
[0011] Preferably, the interface regulator is one or more of graphene oxide or silane coupling agent.
[0012] Preferably, the processing aid comprises a dispersant and a toughening agent, the dispersant is polyethylene glycol, and the toughening agent is ethylene propylene diene monomer rubber.
[0013] Preferably, a method for preparing a special material for motor lead wires comprises the following steps: S1, surface modification of nano-scale low dielectric constant fillers and interface regulators by solvent dispersion; S2, adding a polyimide matrix material, a surface-modified nanometer-level low dielectric constant filler, a micrometer-level reinforcing filler, a conductive filler and a processing aid into a twin-screw extruder in proportion, and kneading for 30-45 minutes at a temperature range of 280-300° C. to obtain a composite material; S3. Place the mixed composite material in a hot pressing mold with a molding temperature of 280-300°C, a molding pressure of 5-10MPa, and a heat preservation time of 30-60min.
[0014] Preferably, the solvent in step S1 is ethanol or acetone, and the mass ratio of the solvent to the nanoscale low dielectric constant filler is 10:1.
[0015] Preferably, during the mixing process, the micron-sized reinforcing filler is first added, and the mixing time is 10-15 minutes; then the nano-sized low dielectric constant filler is added, and the mixing time is 15-20 minutes; finally, the conductive filler and the interface regulator are added, and the mixing time is 5-10 minutes.
[0016] The present invention provides a special material for motor lead wires, which has the following beneficial effects: 1. The present invention achieves the technical effect of reducing dielectric constant and leakage current by adopting the technical solution of composite surface-modified silica nanoparticles with polyimide matrix. Compared with the technical solution of directly using unmodified fillers in the prior art, the present invention improves the dispersibility and interface bonding of particles by modifying fillers, and solves the shortcomings of the prior art that the dielectric constant is high and the leakage current is large due to the interface polarization and uneven distribution of fillers.
[0017] 2. The present invention uses silver nanowires as conductive fillers and constructs a stable conductive network through its high aspect ratio, achieving the technical effect of improving conductivity and taking into account insulation performance at low filler content. Compared with the technical solution of using zero-dimensional fillers such as carbon black to construct conductive paths in the prior art, the present invention effectively reduces the percolation threshold of the conductive network and solves the shortcomings of the prior art that high filler content leads to reduced insulation and unstable conductive network.
[0018] 3. The present invention uses aluminum oxide micron particles as reinforcing fillers and combines the interface regulator to improve the bonding between the filler and the matrix, thereby achieving the technical effect of increasing the thermal decomposition temperature of the material and reducing the thermal expansion coefficient. Compared with the technical solution of using traditional reinforcing fillers such as glass fiber in the prior art, the present invention solves the problems of weak interface bonding, high temperature cracking and uneven thermal expansion in the prior art by optimizing the interface between the filler and the matrix.
[0019] 4. The present invention achieves the technical effect of significantly improving tensile strength and impact strength by adopting the technical solution of synergistic enhancement of aluminum oxide micron particles and interface regulators. Compared with the technical solution in the prior art that only relies on increasing the amount of filler added to improve mechanical properties, the present invention enhances the compatibility of fillers and substrates through interface regulators, solving the shortcomings of the prior art that poor mechanical properties are caused by uneven filler distribution and insufficient interface bonding. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION
[0021] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Please refer to the attached Figure 1 The embodiment of the present invention provides a special material for motor lead wires, which includes the following components by weight percentage: polyimide matrix material: 50-70%, nano-level low dielectric constant filler: 5-12%, micron-level reinforcing filler: 10-20%, conductive filler: 3-8%, interface regulator 0.5-2%, and processing aid 1-3%.
[0023] The polyimide matrix material is a fluorine-containing polymer, and the fluorine-containing polymer is polytetrafluoroethylene, perfluoroethylene propylene or a mixture thereof.
[0024] The nano-scale low dielectric constant filler is silicon dioxide particles with a particle size of 10-50 nm, and the silicon dioxide particles are surface-modified by a silane coupling agent.
[0025] The micron-sized reinforcing filler is aluminum oxide particles, and the particle size of the aluminum oxide particles ranges from 1 to 10 μm.
[0026] The conductive filler is one or more of carbon nanotubes, graphene or silver nanowires.
[0027] The interface regulator is one or more of graphene oxide and silane coupling agent.
[0028] The processing aid comprises a dispersant and a toughening agent, wherein the dispersant is polyethylene glycol and the toughening agent is ethylene propylene diene monomer rubber.
[0029] A method for preparing a special material for a motor lead wire comprises the following steps: S1, surface modification of nano-scale low dielectric constant fillers and interface regulators by solvent dispersion; S2, adding a polyimide matrix material, a surface-modified nanometer-level low dielectric constant filler, a micrometer-level reinforcing filler, a conductive filler and a processing aid into a twin-screw extruder in proportion, and kneading for 30-45 minutes at a temperature range of 280-300° C. to obtain a composite material; S3, placing the mixed composite material in a hot pressing mold, with a molding temperature of 280-300°C, a molding pressure of 5-10MPa, and a heat preservation time of 30-60min; S4. Cool the formed material to room temperature to obtain a special material for the motor lead wire.
[0030] Embodiment 1; Example 1: Preparation of low dielectric constant insulating material; Implementation purpose; Through low dielectric constant nanofillers and interface control technology, the dielectric constant of composite materials can be reduced, leakage current can be reduced, and insulation performance can be improved; Raw material ratio By mass percentage: Polyimide (PI): 60%; Silica nanoparticles (particle size 20nm): 8%; Alumina micron particles (particle size 5μm): 15%; Carbon nanotubes: 5%; Interface regulator (silane coupling agent KH570): 1%; Processing aid (polyethylene glycol PEG): 1%; Preparation steps: Nanofiller surface modification; Silica nanoparticles were added to the ethanol solution at a mass ratio of 1:10, stirred at 300 rpm, the temperature was controlled at 50 °C, and stirred for 30 min; Add KH570 silane coupling agent to the ethanol solution at a mass ratio of 3% of the nanofiller and continue stirring for 30 min; After dispersion treatment under 40kHz ultrasonic conditions for 30min, the solution was vacuum dried at 100°C for 6h to obtain modified silica nanoparticles. Mixing process; The polyimide matrix material was dried in vacuum at 300°C for 4 h and then added into a twin-screw extruder for melting; Alumina micron particles (mixing time 10 min), modified SiO2 (mixing time 15 min) and a mixture of carbon nanotubes and processing aids (mixing time 10 min) were added in sequence. The screw speed was 40 rpm and the total mixing time was 35 min. Thermoforming; The mixed melt was placed in a hot pressing mold at a molding temperature of 300°C and a pressure of 8MPa for 40 minutes; After compression molding, the mold is cooled to room temperature and demoulded to obtain the special material for motor lead wires; Through uniform dispersion and interface regulation of nanometer-scale low dielectric constant fillers, this embodiment significantly reduces the dielectric constant of the composite material and solves the problem of high leakage current in the prior art.
[0031] Example 2: Preparation of highly conductive insulating composite material; Implementation purpose; Through the optimized distribution of conductive fillers, a microscopic conductive network is constructed to achieve a synergistic balance between conductivity and insulation; Raw material ratio By mass percentage: Polyimide (PI): 65%; Silica nanoparticles (particle size 30nm): 6%; Alumina micron particles (particle size 8μm): 12%; Silver nanowire (AgNW): 7%; Interface regulator (graphene oxide GO): 1%; Processing aids: 1%; Preparation steps: Nanofiller surface modification; Silica nanoparticles were added to the acetone solution (mass ratio 1:10), stirred at 200 rpm, the temperature was controlled at 40 °C, and the stirring time was 20 min; Graphene oxide (mass ratio is 1% of silicon dioxide) was added, ultrasonically dispersed for 40 min and then dried; Mixing process; The polyimide material, modified silica nanoparticles and alumina particles were added into a twin-screw extruder in proportion, the mixing temperature was 280°C and the screw speed was 50 rpm; 15 minutes after mixing, silver nanowires were gradually added and mixing was continued for 10 minutes, with a total time of 30 minutes; Thermoforming; The mixed melt was pressed into a mold at 280°C and 5MPa, kept warm for 30 minutes, and then cooled and demolded; Through the synergistic effect of silver nanowires and interface regulators, this embodiment significantly improves the conductive properties while maintaining the insulating properties, solving the problem in the prior art that conductivity and insulation cannot be achieved at the same time.
[0032] Example 3: Preparation of composite materials that operate stably in high temperature environments; Implementation purpose; Improve the mechanical and electrical properties of the material in high temperature environments through the enhanced synergistic effect of micron-sized fillers and polyimide matrix; Raw material ratio By mass percentage: Polyimide (PI): 55%; Alumina micron particles (particle size 5μm): 20%; Modified silica (particle size 15nm): 8%; Carbon nanotubes (CNT): 6%; Interface regulator (silane coupling agent KH570): 1%; Processing aids: 2%; Preparation steps: Alumina and silica modification; Alumina and silica particles were surface modified using KH570, added to an ethanol solution and stirred (300 rpm) for 30 min, followed by ultrasonic treatment for 20 min, and dried at 100 °C for 4 h; Mixing process; After the polyimide matrix was melted at 300°C, aluminum oxide microparticles were added and mixed for 10 min; Modified silica and carbon nanotubes were gradually added, with mixing times of 10 min and 15 min, respectively, and a total mixing time of 35 min; Thermoforming; The mixture was hot pressed at 300°C and 10 MPa for 40 min and then cooled to form; Through the reinforcing effect of the micron-sized alumina filler, this embodiment improves the mechanical properties and electrical stability of the composite material in a high temperature environment, and solves the problem of material performance degradation at high temperatures in the prior art; Example 4: Preparation of composite materials with optimized mechanical properties; Implementation purpose; Improve the mechanical strength and impact resistance of materials through the synergistic effect of micron-scale reinforcing fillers and interface regulators; Raw material ratio By mass percentage: Polyimide (PI): 58%; Alumina micron particles (particle size 3μm): 18%; Silicon dioxide (particle size 10nm): 10%; Interface regulator (graphene oxide): 1.5%; Processing aid (toughening agent EPDM): 2.5%; Preparation steps: Filler modification; Alumina particles were added to ethanol and dispersed together with graphene oxide, and then dried after ultrasonic treatment for 30 min. Mixing and molding; The polyimide matrix and the modified filler were mixed in a twin-screw extruder at 280°C for a total mixing time of 40 min, and the filler was added in stages; The hot pressing conditions were 290°C, 8MPa, and the holding time was 35min; This embodiment significantly improves the mechanical properties by optimizing the bonding interface between the micron filler and the matrix, and solves the problem of uneven material strength caused by filler agglomeration in the prior art.
[0033] Comparative Example 1: Comparison with Example 1 (low dielectric constant insulating material); the difference; In Comparative Example 1, no surface-modified nanofiller was used, and unmodified silica particles were directly added; Preparation process Ratio of raw materials; By mass percentage: Polyimide (PI): 60%; Silica particles (particle size 20 nm, unmodified): 8%; Alumina micron particles (Al2O3, particle size 5 μm): 15%; Carbon nanotubes (CNT): 5%; Processing aid (PEG): 1% Preparation steps: Direct use of unmodified fillers: The silica particles were not surface modified and were directly added to ethanol, stirred and dispersed, and then dried after ultrasonic treatment for 20 min; Mixing process: The mixing process of Example 1 was followed, with the same temperature, pressure and time conditions.
[0034] Thermoforming: The hot pressing process of Example 1 was followed.
[0035] Comparative Example 2: Comparison with Example 2 (highly conductive insulating composite material); the difference; In Comparative Example 2, silver nanowires were not used as conductive fillers, but traditional carbon black fillers were used; Preparation process Ratio of raw materials; By mass percentage: Polyimide (PI): 65%; Silica particles (particle size 30nm, modified): 6%; Alumina micron particles (particle size 8μm): 12%; Carbon black (instead of silver nanowires): 7%; Interface regulator (graphene oxide GO): 1%; Processing aids: 1%; Preparation steps Nanofiller surface modification; Similar to Example 2, the silicon dioxide particles are modified and dried for later use; Mixing process: The polyimide matrix material was mixed with modified silica and alumina particles, and then carbon black was added as a conductive filler. The mixing temperature was 280° C. and the total time was 30 min. Other conditions were the same as those in Example 2. Thermoforming: The operation is carried out according to the hot pressing process of Example 2.
[0036] Comparative Example 3: Comparison with Example 3 (composite material stably operating under high temperature environment); the difference; In Comparative Example 3, instead of using aluminum oxide micron particles as reinforcing filler, the same mass of unmodified glass fibers were used; Preparation process Ratio of raw materials; By mass percentage: Polyimide (PI): 55%; Unmodified glass fiber (particle size 3-8μm): 20%; Modified silica (particle size 15nm): 8%; Carbon nanotubes (CNT): 6%; Interface regulator (KH570): 1%; Processing aids: 2%; Preparation steps Direct use of glass fiber: The glass fiber particles are directly compounded with the polyimide matrix and other fillers without modification.
[0037] Mixing process: The polyimide matrix, glass fiber, silicon dioxide and carbon nanotubes were mixed according to the process parameters of Example 3, with a mixing temperature of 300° C. and a mixing time of 35 min.
[0038] Thermoforming: The operation was carried out according to the hot pressing process of Example 3.
[0039] Comparative Example 4: Comparison with Example 4 (Composite Material with Optimized Mechanical Properties) the difference In comparative example 4, no interface modifier is added, and the aluminum oxide micron particles and the silicon dioxide nanoparticles are directly added to the matrix and mixed; Preparation process Ratio of raw materials; By mass percentage: Polyimide (PI): 58%; Alumina micron particles (particle size 3μm): 18%; Silicon dioxide (particle size 10nm): 10%; Processing aid (toughening agent EPDM): 2.5% Preparation steps Mixing without interfacial regulators; Alumina particles and silica particles are directly mixed with the polyimide matrix material without surface modification.
[0040] Mixing process; The mixing conditions were the same as those in Example 4, using a twin-screw extruder, a mixing temperature of 280° C., and a mixing time of 40 min.
[0041] Thermoforming: The operation was carried out according to the hot pressing process of Example 4.
[0042] Comparative Example 5: Commonality comparison for all embodiments the difference No nanofillers are used, only the traditional combination of polyimide matrix and micron-sized fillers is adopted; Preparation process Raw material ratio by mass percentage: Polyimide (PI): 70%; Alumina micron particles (particle size 5μm): 20%; Processing aids: 2%.
[0043] Preparation steps No nanofillers used: No nanofillers such as silica or carbon nanotubes are added.
[0044] Mixing process: Only the polyimide matrix and the alumina particles were mixed, with a total mixing time of 20 min and a temperature of 280°C.
[0045] Thermoforming: The molding conditions were the same as those in the example.
[0046] Experiment 1: Insulation performance test (dielectric constant and leakage current) Experimental description; Purpose of the experiment; The insulation properties (dielectric constant and leakage current) of Example 1, Comparative Example 1 and Comparative Example 5 were tested to verify the advantages of surface-modified nanofillers in reducing dielectric constant and leakage current; Experimental Materials Example 1: Using surface modified silicon dioxide nanoparticles as filler; Comparative Example 1: Using unmodified silica nanoparticles; Comparative Example 5: only containing aluminum oxide micron particles, without nano filler; Experimental equipment LCR digital bridge: used to measure the dielectric constant of the sample, the frequency range is 1kHz-1MHz.
[0047] High resistance meter: used to measure leakage current, voltage range 0-500V Experimental procedures Sample preparation: The composite materials of Example 1, Comparative Example 1 and Comparative Example 5 were cut into round pieces with a diameter of 50 mm and a thickness of 1 mm. Five pieces of the samples were prepared.
[0048] Dielectric constant test: The sample was placed between the test electrodes of the LCR bridge and the dielectric constant was tested at 1kHz, 100kHz and 1MHz at room temperature.
[0049] The sample was measured 3 times and the average value was taken; Leakage current test: Place the sample between the electrodes of the high resistance meter and gradually apply DC voltage, starting from 0V, and test the leakage current at 50V, 100V, 300V and 500V in sequence.
[0050] The sample was measured 3 times and the average value was taken; Data recording and processing: Record the dielectric constant and leakage current of each sample at different frequencies and voltages, and calculate the average value; Experimental data; Table name: Dielectric constant and leakage current test results table;
[0051] Experimental summary (including mechanism analysis) This experiment verifies the superiority of Example 1 in terms of insulation performance over Comparative Example 1 and Comparative Example 5 by testing the dielectric constant and leakage current. The experimental results show that the dielectric constant of Example 1 is significantly lower than that of Comparative Example 1 and Comparative Example 5, and the leakage current is also greatly reduced. The following is a mechanism analysis and summary: The surface modified nanofiller (such as silicon dioxide) used in the present invention significantly optimizes the dielectric properties of the matrix material. The modified silicon dioxide introduces a functional group with low polarity (such as an organosilane group) on the particle surface through a silane coupling agent, thereby enhancing the compatibility between the nanofiller and the polyimide matrix. This modification effectively suppresses the interface polarization phenomenon inside the material. According to the interface polarization theory, when the interface defects are reduced, the polarization intensity between the filler and the matrix will be significantly reduced, thereby reducing the dielectric constant as a whole. However, the unmodified nanofiller in comparative example 1 causes poor bonding with the matrix interface, and the interface polarization phenomenon is more significant, thereby showing a higher dielectric constant and leakage current.
[0052] In addition, Comparative Example 5 only uses micron-sized fillers, and there is no synergistic effect of nanofillers at all, so its electric field distribution uniformity is poor and the polarization effect is more significant. According to Maxwell's equations, when the size of the filler is reduced to the nanoscale, the electric field concentration effect inside the material can be significantly reduced. However, due to the larger particle size of micron fillers, the electric field concentration effect is more obvious, which further increases the leakage current.
[0053] From the results, the difference in the leakage current test also reveals the advantages of surface-modified nanofillers. In Example 1, the uniformly dispersed nanofillers and the matrix formed a highly stable insulation network, reducing the conductive path inside the material. In Comparative Example 1, the agglomeration of the unmodified filler formed a local conductive path, resulting in an increase in leakage current; in Comparative Example 5, there was a complete lack of nanofillers, the insulation network performance was even worse, and the leakage current increased significantly.
[0054] Experiment 2: Conductivity test (conductivity); Experimental description; Purpose of the experiment; Verify the superiority of the present invention in balancing conductivity and insulation, and highlight the innovation of the present invention in constructing a uniform conductive network by comparing the conductivity of Example 2 with that of Comparative Example 2. Experimental materials; Example 2: Using silver nanowires as conductive fillers and combining them with an interface regulator to improve the uniformity of filler dispersion; Comparative Example 2: Using carbon black (traditional conductive filler), a uniform conductive network was not formed; Experimental equipment; Four-probe resistance tester: used to measure the surface resistivity of samples and calculate conductivity; Cutting tools: Cut samples to standard size; Experimental procedures; Sample preparation; The composite materials of Example 2 and Comparative Example 2 were cut into rectangular samples with a size of 50 mm×10 mm×1 mm, and five samples were prepared; Test steps: The samples were tested using a four-probe resistance tester.
[0055] Place the sample between the probes, adjust the probe spacing in sequence, and record the resistance value under different test conditions; Experimental setup; Test temperature: room temperature; Each sample was tested repeatedly at three different probe spacings, and the average value was taken; Comparative analysis of the difference in conductivity between Example 2 and Comparative Example 2; Experimental data; Table name: Conductivity test result table;
[0056] Experimental summary (including mechanism analysis) Through the conductivity test of Example 2 and Comparative Example 2, it is found that Example 2 using silver nanowires exhibits significantly higher conductivity, especially under high current conditions, its conductivity remains stable, while Comparative Example 2 exhibits a significant decrease in conductivity. Combined with the mechanism analysis, the technical advantages of the present invention in improving conductivity are described below.
[0057] The present invention constructs a highly uniform and continuous conductive network structure by using silver nanowires as conductive fillers. Silver nanowires have the advantages of one-dimensional nanostructures, can form efficient conductive paths in composite materials, and are tightly combined with the matrix material. The formation of this network structure benefits from the aspect ratio of silver nanowires, and can achieve the continuity of the conductive path at a lower filler content. The carbon black used in Comparative Example 2 is a zero-dimensional particle filler, and the conductivity between its particles depends on the particle packing density. Therefore, it is easy to cause the conductive path to break due to uneven distribution of fillers or insufficient filling, and the conductive performance is significantly reduced, especially under high current conditions.
[0058] In addition, from the perspective of percolation theory, the amount of silver nanowires added in the present invention is close to or exceeds the critical percolation threshold of the conductive network, ensuring the stability of the conductive path. However, the carbon black filler in Comparative Example 2 has a small contact area between particles, so even if the amount of filler added is close to the critical percolation threshold, gaps may still appear in the conductive path, resulting in unstable or even degraded conductive performance.
[0059] Further analysis shows that the surface resistance of silver nanowires is low, and their conductivity is more stable under high current conditions. This is related to their metallic properties and the nature of high conductivity materials, while carbon black may further reduce its conductivity under high current conditions due to increased interface contact resistance.
[0060] Experiment 3: Heat resistance test (thermal decomposition temperature and thermal expansion coefficient) Experimental description; Purpose of the experiment; The heat resistance of Example 3, Comparative Example 3 and Comparative Example 5 was tested, and the high temperature stability advantage of the aluminum oxide reinforced filler of the present invention was verified by comparing the thermal decomposition temperature and the thermal expansion coefficient; Experimental Materials Embodiment 3: Using aluminum oxide micron particles as reinforcing filler; Comparative Example 3: Using unmodified glass fiber to replace alumina filler; Comparative Example 5: Only using traditional micron fillers without nano fillers; Experimental equipment; Thermogravimetric Analyzer (TGA): used to test the thermal decomposition temperature of materials; Thermomechanical Analyzer (TMA): used to test the thermal expansion coefficient of materials; Experimental procedures; Sample preparation: The composite materials of Example 3, Comparative Example 3 and Comparative Example 5 were prepared and cut into the following specifications: Thermal decomposition temperature test: 10 mm × 10 mm × 2 mm small piece; Thermal expansion coefficient test: 50mm×10mm×2mm strip sample; Prepare 3 samples to ensure test repeatability; Thermal decomposition temperature test (TGA): The sample was placed in a thermogravimetric analyzer and heated from room temperature to 600°C at a rate of 10°C / min, and the mass change of the sample was recorded; Measure the initial decomposition temperature of the sample (the temperature at which 5% mass loss occurs); Thermal expansion coefficient test (TMA): The sample was placed in a thermomechanical analyzer with a temperature range of 30°C to 300°C and a heating rate of 5°C / min. Record the length change of the sample at different temperatures and calculate the thermal expansion coefficient; Data recording and processing: The sample was tested 3 times, the results were recorded and the average was taken; Experimental data; Table name: Heat resistance test results table;
[0061] Experimental summary (including mechanism analysis) It can be seen from the experimental data that Example 3 is superior to Comparative Examples 3 and 5 in terms of thermal decomposition temperature and thermal expansion coefficient. This shows that the aluminum oxide micron filler used in the present invention plays a significant role in improving material stability and inhibiting thermal expansion under high temperature environment, while the performance of unmodified glass fiber and traditional micron filler alone is insufficient. The following is a detailed description combined with mechanism analysis.
[0062] The present invention constructs a good filler-matrix reinforcement structure by introducing aluminum oxide micron particles into a polyimide matrix. Alumina, as a highly heat-resistant material, has a melting point close to 2000°C and has excellent thermal stability in composite materials. When the material is subjected to external heat load at high temperature, the aluminum oxide particles delay the decomposition process of the matrix material by absorbing part of the heat and dispersing thermal stress. Therefore, the thermal decomposition temperature in Example 3 is significantly higher than that in Comparative Example 3 and Comparative Example 5. The glass fiber filler used in Comparative Example 3 cannot effectively prevent the decomposition of the matrix material due to its low melting point and insufficient bonding with the matrix interface. Comparative Example 5 further reduces its thermal stability due to the lack of reinforcing fillers.
[0063] In terms of thermal expansion performance, the present invention significantly reduces the thermal expansion coefficient of the material by using alumina particles. According to the thermal expansion theory of composite materials, the difference between the volume fraction of the filler, the thermal expansion coefficient and the matrix determines the overall thermal expansion behavior of the composite material. The thermal expansion coefficient of alumina particles is much lower than that of the polyimide matrix. Through the synergistic effect of the filler and the matrix, the overall expansion of the material can be effectively reduced. However, the glass fiber in comparative example three cannot effectively transfer thermal stress due to its weak interfacial bonding with the matrix, resulting in a high expansion coefficient; comparative example five further deteriorates the dimensional stability at high temperature due to the lack of nano-scale fillers.
[0064] In addition, the interface modifier in the present invention further improves the dispersion of the alumina particles in the matrix, enabling them to evenly bear and disperse thermal stress, and prevent microstructural damage caused by local thermal stress concentration. However, comparative examples 3 and 5 have more interface defects, poor thermal stress transfer efficiency, and show a higher thermal expansion coefficient.
[0065] Experiment 4: Mechanical properties test (tensile strength and impact strength) Experimental Description Purpose The mechanical properties (tensile strength and impact strength) of Example 4, Comparative Example 4 and Comparative Example 5 were tested to verify the technical advantage of the synergistic effect of the aluminum oxide micron filler and the interface regulator in the present invention in improving the mechanical properties; Experimental Materials Example 4: Using aluminum oxide micron particles and interface regulator (graphene oxide) as composite fillers; Comparative Example 4: No interface regulator was added, and only aluminum oxide micron particles were used; Comparative Example 5: Only traditional micron fillers were used without adding nano-scale fillers or interface regulators; Experimental equipment Universal material testing machine: used to test the tensile strength of materials; Simple supported beam impact testing machine: used to test the impact strength of materials; Experimental procedures; Sample preparation: The composite materials of Example 4, Comparative Example 4 and Comparative Example 5 were prepared and cut into the following sizes respectively: Tensile strength test: 100mm×10mm×2mm strip sample; Impact strength test: 80 mm × 10 mm × 4 mm rectangular sample.
[0066] Prepare 5 samples to ensure test repeatability; Tensile strength test: According to GB / T1040 standard, the strip sample was clamped in a universal material testing machine and stretched to fracture at a constant tensile rate of 2 mm / min.
[0067] Record the maximum tensile load of the sample and calculate the tensile strength (unit: MPa); Impact strength test: According to GB / T1043 standard, the impact strength of the sample is tested on a simply supported beam impact testing machine (unit: kJ / m²); The impact direction of the sample is perpendicular to the thickness direction, and the impact energy absorbed by the sample is recorded; Data recording and processing: The sample was tested 3 times, the data was recorded and the average value was calculated; Experimental data; Table name: Mechanical properties test results table;
[0068] Experimental summary (including mechanism analysis) This experiment tested the differences in tensile strength and impact strength between Example 4, Comparative Example 4 and Comparative Example 5. The experimental results showed that the mechanical properties of Example 4 were significantly better than those of Comparative Example 4 and Comparative Example 5, which fully demonstrated the technical advantages of the present invention in enhancing the mechanical properties of materials. The following is a detailed summary of the experimental results and technical mechanisms combined with mechanism analysis.
[0069] Example 4 significantly improves the tensile strength and impact strength of the material by introducing alumina micron particles and interface regulator (graphene oxide). Alumina particles, as reinforcing fillers, can effectively improve the rigidity and strength of the matrix, while the role of the interface regulator is to optimize the bonding interface between the filler and the matrix. Graphene oxide has abundant polar functional groups, such as hydroxyl (-OH) and carboxyl (-COOH), which can form chemical bonds or strong interactions with alumina particles and polyimide matrix, significantly improving the adhesion strength of the interface. Good interface bonding can effectively transfer stress and reduce the stress concentration effect of interface defects, thereby greatly improving the tensile strength and toughness of the material.
[0070] In Comparative Example 4, although aluminum oxide micron particles were added, the interface bonding between the filler and the matrix was weak due to the lack of an interface regulator, resulting in low stress transfer efficiency. When the material is subjected to tensile or impact loads, microcracks are more likely to propagate at the interface, limiting further improvement of mechanical properties. Comparative Example 5 only uses traditional micron fillers, lacks the reinforcement effect of nano-scale fillers, and has worse inter-particle interface forces, ultimately showing the lowest tensile strength and impact strength.
[0071] From the perspective of the mechanism of mechanical properties, the dispersibility and particle size of the filler are key factors affecting the performance of the composite material. In Example 4, due to the effect of the interface regulator on the surface of the alumina particles, its dispersibility in the matrix is significantly improved, and the filler can be evenly distributed throughout the composite material to form a uniform stress dispersion network. However, the traditional micron filler in Comparative Example 5 has a large particle size and uneven distribution, resulting in stress concentration areas inside the material, accelerating the destruction process, and thus showing poor mechanical properties.
[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A special material for motor lead wire, characterized in that: Calculated by weight percentage, it includes the following components: polyimide matrix material: 50-70%, nanometer-level low dielectric constant filler: 5-12%, micron-level reinforcing filler: 10-20%, conductive filler: 3-8%, interface regulator 0.5-2%, and processing aid 1-3%.
2. The special material for motor lead wire according to claim 1, characterized in that: The polyimide matrix material is a fluorine-containing polymer, and the fluorine-containing polymer is polytetrafluoroethylene, perfluoroethylene propylene or a mixture thereof.
3. The special material for motor lead wire according to claim 1, characterized in that: The nano-scale low dielectric constant filler is silicon dioxide particles with a particle size of 10-50 nm, and the silicon dioxide particles are surface-modified by a silane coupling agent.
4. The special material for motor lead wire according to claim 1, characterized in that: The micron-sized reinforcing filler is aluminum oxide particles, and the particle size of the aluminum oxide particles ranges from 1 to 10 μm.
5. The special material for motor lead wire according to claim 1, characterized in that: The conductive filler is one or more of carbon nanotubes, graphene or silver nanowires.
6. The special material for motor lead wire according to claim 1, characterized in that: The interface regulator is one or more of graphene oxide and silane coupling agent.
7. The special material for motor lead wire according to claim 1, characterized in that: The processing aid comprises a dispersant and a toughening agent, wherein the dispersant is polyethylene glycol and the toughening agent is ethylene propylene diene monomer rubber.
8. A method for preparing a special material for motor lead wires, according to the special material for motor lead wires according to any one of claims 1 to 7, characterized in that: The steps include: S1, surface modification of nano-scale low dielectric constant fillers and interface regulators by solvent dispersion; S2, adding a polyimide matrix material, a surface-modified nanometer-level low dielectric constant filler, a micrometer-level reinforcing filler, a conductive filler and a processing aid into a twin-screw extruder in proportion, and kneading for 30-45 minutes at a temperature range of 280-300° C. to obtain a composite material; S3, placing the mixed composite material in a hot pressing mold, with a molding temperature of 280-300°C, a molding pressure of 5-10MPa, and a heat preservation time of 30-60min; S4. Cool the formed material to room temperature to obtain a special material for the motor lead wire.
9. The method for preparing a special material for motor lead wire according to claim 8, characterized in that: The solvent in step S1 is ethanol or acetone, and the mass ratio of the solvent to the nano-scale low dielectric constant filler is 10:
1.
10. The method for preparing a special material for motor lead wire according to claim 8, characterized in that: During the mixing process, firstly, the micron-level reinforcing filler is added, and the mixing time is 10-15 minutes; then, the nano-level low dielectric constant filler is added, and the mixing time is 15-20 minutes; finally, the conductive filler and the interface regulator are added, and the mixing time is 5-10 minutes.
Citation Information
Patent Citations
Transparent polyimide film and preparation method thereof
CN104672901A
Preparation method of polyimide film
CN106008975A
Heat-proof and high-strength polyimide film
CN106084221A
Longitudinal high-thermal-conductivity gasket, preparation method and application
CN113321933A
High-strength high-filling-amount polyimide resin wave-absorbing adhesive film and preparation method thereof
CN117659456A
Cited By
Radio frequency microwave test cable and preparation method thereof
CN121565591A